Infant Pain Regulation as an Early Indicator of Childhood Temperament. (2013) - Stevens, Sara A; Racine, Nicole; Riddell, Rebecca Pillai; Horton, Rachel; Garfield, Hartley; Greenberg, Saul
Abstract : BACKGROUND: There is considerable variability in infants' responses to painful stimuli, including facial and vocal expressions. This variability in pain-related distress response may be an indicator of temperament styles in childhood. OBJECTIVE: To examine the relationships among immunization pain outcomes (pain reactivity, pain regulation and parent ratings of infant pain) over the first year of life and parent report of early temperament. METHODS: A subset of parent-infant dyads in an ongoing Canadian longitudinal cohort was studied. Infant pain behaviours were coded using the Modified Behavior Pain Scale. Parental judgments of infant pain were recorded using the Numeric Rating Scale. Infant temperament was measured using the Infant Behaviour Questionnaire-Revised. Correlational analyses and multiple regressions were conducted. RESULTS: Multiple regressions revealed that the 12-month regulatory pain scores predicted parent ratings of the Negative Affectivity temperament dimension at 14 months of age. Parent ratings of infant pain at 12 months of age predicted parent ratings of the Orienting/Affiliation temperament dimension, with sex differences observed in this substrate. CONCLUSION: Pain-related distress regulation at one year of age appears to be a novel indicator of parent report of temperament ratings. Pain outcomes in the first six months of life were not related to parent temperament ratings.